Intranasal Glomus Tumor- A Case Report - Badruddoza, SM; Asafudullah, SM (TAJ: Journal of Teachers Association, 2009)
A thirty five years old man, reported at ENT Department SZMC, Bogra, and sent to private laboratory in Rajshahi July 2009 with 6 month history of left sided nasal obstruction, pain and intermittent epistaxis. Physical examination revealed a large polyp-like mass protruding from left nose. Histopathology revealed the picture of glomus tumor. TAJ 2009; 22(1): 255-256